Cancelloplasty for Treatment of Osteomyelitis of the Calcaneus: A Novel Technique and Case Report. Issue 3 (June 2021) - Huchital, Michael J.; Saleh, Ali; Patel, Rajan; Subik, Michael
Calcaneal osteomyelitis has the potential to cause limb- and life-threatening complications. The anatomic and biomechanical attributes of the heel make limb salvage in the setting of bone infection complex. Current treatment options include surgical resection of part or all of the calcaneus, lower extremity amputation, or prolonged intravenous antibiotic usage. Each modality has its own inherent disadvantages. We present a novel surgical technique using antibiotic-impregnated calcium phosphate as an alternative treatment option coupled with ultrasonic bone dissection as a method for enhancing delivery of antibiotics, while mitigating tissue damage and maintaining osseous integrity. The details of the surgical technique are discussed along with a single case example.